1999
DOI: 10.1091/mbc.10.2.487
|View full text |Cite
|
Sign up to set email alerts
|

The Stem-Loop Binding Protein (SLBP1) Is Present in Coiled Bodies of the Xenopus Germinal Vesicle

Abstract: The stem-loop binding protein (SLBP1) binds the 3Ј stem-loop of histone pre-mRNA and is required for efficient processing of histone transcripts in the nucleus. We examined the localization of SLBP1 in the germinal vesicle of Xenopus laevis oocytes. In spread preparations of germinal vesicle contents, an anti-SLBP1 antibody stained coiled bodies and specific chromosomal loci, including terminal granules, axial granules, and some loops. After injection of myc-tagged SLBP1 transcripts into the oocyte cytoplasm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 49 publications
1
41
0
Order By: Relevance
“…There thus appears to be a large excess of SLBP in the mature oocyte and early embryo, compared with the need for SLBP for synthesis and translation of histone mRNA. This taken together with the expression of SLBP throughout the cell cycle open the possibility that SLBP may perform other functions not directly linked to histone mRNA metabolism (Abbott et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…There thus appears to be a large excess of SLBP in the mature oocyte and early embryo, compared with the need for SLBP for synthesis and translation of histone mRNA. This taken together with the expression of SLBP throughout the cell cycle open the possibility that SLBP may perform other functions not directly linked to histone mRNA metabolism (Abbott et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In the cell, much of the U7 snRNP is found in Cajal (coiled) bodies, "spheres" in Xenopus oocytes (Wu & Gall, 1993;Wu et al+, 1996), and these nuclear organelles are located near the histone genes in oocytes (Callan et al+, 1991) and in mammalian cells (Frey & Matera, 1995;Matera, 1999), suggesting a role for the coiled bodies in histone pre-mRNA processing+ Some of the xSLBP1 in the frog oocyte is also located in the spheres (Abbott et al+, 1999)+ One possibility is that xSLBP1 may function in a distinct subnuclear compartment+ The histone genes have remained tightly clustered throughout evolution, suggesting that there is selective pressure keeping them closely linked (Wang et al+, 1996a(Wang et al+, , 1996b)+ One reason for this tight clustering may be that the genes are localized in a region of the nucleus specific for histone mRNA processing+ Ninety-five percent of the U7 snRNA in the Xenopus oocyte nucleus is present in spheres (Wu & Gall, 1993)+ Spheres are found dispersed in the nucleoplasm and some are physically attached to the chromosomes at histone gene loci in amphibian oocyte lampbrush chromosome spreads (Callan et al+, 1991)+ Recently Gall and coworkers have shown that xSLBP1 is present in the spheres of the amphibian germinal vesicle (Abbott et al+, 1999)+ A region of xSLBP1, including part of the RBD and the C-terminal region, is capable of directing the xSLBP1 to coiled bodies (Abbott et al+, 1999)+ The spheres also contain RNA polymerase II and coilin (Bellini & Gall, 1998), which has also been shown to associate with the U7 snRNP (Bellini & Gall, 1998)+ Localization of xSLBP1 to the spheres (coiled bodies) may be important for efficient histone pre-mRNA processing in vivo+ The 1-2-1 protein may be deficient in localizing to the coiled bodies or may not interact with unknown factor(s) necessary for processing in vivo, but not in vitro+ In nuclear extracts, any nuclear substructures are disrupted allowing interaction of factors that may be physically separated in the nucleus in vivo+ It is also likely that histone premRNA processing is coupled to histone gene transcription in vivo, as is polyadenylation (McCracken et al+, 1997)+ Thus in vivo there may be a defined pathway by which the histone pre-mRNA processing machinery is assembled and this pathway could be disrupted in nuclear extracts+ Differences in metabolism of the same RNA molecule transcribed from a gene and injected into the nucleoplasm are likely to be observed in many cases+ Differences in the "masking" of mRNAs have been observed in Xenopus oocytes depending on whether synthetic pre-mRNA was injected or whether the premRNA was expressed from an injected gene (Meric et al+, 1996;Matsumoto et al+, 1998)+ It is likely that many steps in nuclea...…”
Section: The Xslbp1 Rna Binding Domain Has Multiple Functionsmentioning
confidence: 99%
“…In addition, a subset of state-dependent mRNAs was common to two or more brain regions [Cirelli et al, 2004;Terao et al, 2006], suggesting that sleep influences global as well as regional brain function(s). While these studies provided valuable insights regarding the intracellular impact of sleep at the nucleic acid level, alterations in mRNA levels often do not reflect corresponding protein expression [Anderson and Seilhamer, 1997;Abbott et al, 1999;Gygi et al, 1999;Ideker et al, 2001;Takahashi, 2004], a more direct functional indicator of the cellular response to sleep. Additionally, few sleep studies have correlated mRNA and protein expression [Neuner-Jehle et al, 1995;Greco et al, 1999;Guzman-Marin et al, 2006]; thus, the temporal relationship between sleep and protein expression is also unclear.…”
mentioning
confidence: 99%